Consumption of Quercetin and Quercetin-Containing Apple and Cherry Extracts Affects Blood Glucose Concentration, Hepatic Metabolism, and Gene Expression Patterns in Obese C57BL/6J High Fat–Fed Mice. Issue 5 (6th April 2016) - Snyder, Sarah M; Zhao, Bingxin; Luo, Ting; Kaiser, Clive; Cavender, George; Hamilton-Reeves, Jill; Sullivan, Debra K; Shay, Neil F
Abstract: Background: Intake of polyphenols and polyphenol-rich fruit extracts has been shown to reduce markers of inflammation, diabetes, and hepatic complications that result from the consumption of a high-fat (HF) diet. Objective: The objective of this study was to determine whether mice fed polyphenol-rich apple peel extract (AE), cherry extract (CE), and quercetin, a phytochemical abundant in fruits including apples and cherries, would modulate the harmful effects of adiposity on blood glucose regulation, endocrine concentrations, and hepatic metabolism in HF-fed C57BL/6J male mice. Methods: Groups of 8-wk-old mice ( n = 8 each) were fed 5 diets for 10 wk, including low-fat (LF; 10% of total energy) and HF (60% of total energy) control diets and 3 HF diets containing polyphenol-rich AE, CE, and quercetin (0.2% wt:wt). Also, an in vitro study used HepG2 cells exposed to quercetin (0–100 μmol/L) to determine whether intracellular lipid accumulation could be modulated by this phytochemical. Results: Mice fed the HF control diet consumed 36% more energy, gained 14 g more body weight, and had ∼50% elevated blood glucose concentrations (all P < 0.05) than did LF-fed mice. Mice fed HF diets containing AE, CE, or quercetin became as obese as HF-fed mice, but had significantly lower blood glucose concentrations after food deprivation (−36%, −22%, −22%, respectively; P < 0.05). Concentrations of serum C-reactive protein were reduced 29% in quercetin-fed mice compared with HF-fed controls ( P < 0.05). A qualitative evaluation of liver tissue sections suggested that fruit phytochemicals may reduce hepatic lipid accumulation. A quantitative analysis of lipid accumulation in HepG2 cells demonstrated a dose-dependent decrease in lipid content in cells treated with 0–100 μmol quercetin/L ( P < 0.05). Conclusions: In mice, consumption of AE, CE, or quercetin appears to modulate some of the harmful effects associated with the consumption of an obesogenic HF diet. Furthermore, in a cell culture model, quercetin was shown to reduce intracellular lipid accumulation in a dose-dependent fashion.